The future of the Estonian energy sector in relation to EU 2050 low carbon economy roadmap - Neeme, Maris (2016)
Estonia has one of the most energy intensive economies in the European Union. Its energy production has historically relied on fossil fuel, namely oil shale. The European Union Roadmap for moving to a competitive low carbon economy by 2050 provides a policy framework for the member states in order to reduce the greenhouse gas emissions in Europe. Based on Hajer’s argumentative approach, this study focused on how the future of energy production is pictured in Estonia in relation to the long term energy and climate policies of the European Union. This study was based on qualitative methodology with semi-structured interviews, participatory observations and document analysis. The findings revealed contrasting perceptions about the energy transition in Estonia. The energy discourse in Estonia was dominated by concerns about social and economic development, wherein the energy transition meant modifications in the existing energy system. Thus, socio-economic importance perceived in the oil shale industry indicate that fossil fuels will remain in the future energy production. Consequently, the environmental impacts are considered in so far as the European Union greenhouse gas reduction objective prescribes to its member states.